Disrupting the familiar family in postcolonial literature - Laubscher, Emma Kate (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2019)
Anne Enright's The Green Road, Petina Gappah's The Book of Memory and Yvonne Adhiambo Owuor's Dust offer various disruptive representations that challenge the normative family, and allow for an excavation of the potency and pervasiveness of the notion of family as an organising social principle, in a postcolonial context. Through these novels' depictions of unorthodox families, it becomes possible to unpack the metaphorical architecture that underpins the normative family "“ by which I mean that social formation which enables and relies upon gender binaries, heteronormative constructions of sexuality and exclusionary racial structures. Additionally, I will attempt to examine the role that the normative family plays in shaping the subject, and determining its avenues of association, through encountering the disruptive possibilities portrayed in Gappah, Owuor and Enright's works. My analysis is concerned with how the family orientates the subject in particular ways that regulate and delimit the subject's means of relating to herself, those who surround her and the historic and mnemonic pasts in which she is embedded. In representing alternate kinship structures, these novels expand the aesthetic and imaginative landscape of the family and allow for new forms of relation to emerge. These transgressive and radical ways of being, knowing and loving have disruptive consequences for those social formations which are structured by, and draw on, the family "“ in particular the nation state. This reworking of the nation state, as well as the destabilisation of the relations between nations states, provides new avenues for inhabiting the postcolonial world. In particular, my reading argues that representations of the unfamiliar family offer different ways of receiving and relating to the self, others, and the past within a social order ruptured by the violent legacies of colonisation.
Keywords: Postcolonialism in literature; Families -- Fiction; Interpersonal relations in literature; Families in literature; Gender identity in literature; Gappah, Petina, 1971- -- Criticism and interpretation; Enright, Anne, 1962- -- Criticism and interpretation; Owuor, Yvonne Adhiambo